Determination of C(5)-C(12) perfluoroalkyl carboxylic acids in river water samples in the Czech Republic by GC-MS after SPE preconcentration - Dufková, Veronika; Čabala, Radomír; Ševčík, Václav (Chemosphere, 2012)
A method employing solid phase extraction followed by gas chromatography-mass spectrometry with negative chemical ionization has been developed for determination of ultratrace concentrations of perfluoroalkyl carboxylic acids in river water. The effects of the experimental parameters, such as the pH, additions of NaCl and an ion-pairing agent (tetraethylammonium bromide) and the kind of the elution agent, on the efficiency of the test acid extraction have been studied. The analyte extraction recoveries and the limits of detection and determination have been found. The method developed has been tested on determinations of perfluoroalkyl carboxylic acids in the waters of the two largest Czech rivers, Vltava and Labe (Elbe). The best extraction results have been attained without any alteration of the sample pH, with an addition of tetrabutylammonium bromide (a concentration of 50 μg mL(-1) in the sample) and using methanol as the elution agent. Under these conditions, the recoveries of the test acids in the spiked real samples are within ranges from 60% to 104% and 53% to 111% for analyte concentration levels of 1.40 ng mL(-1) and 0.14 ng mL(-1), respectively, depending on the lengths of the perfluorinated chains of the acids. In general, the recovery decreases with increasing length of this chain. The method developed exhibits very low limits of detection and determination and the results are fully comparable with those obtained when using more expensive HPLC-MS/MS instrumentation. Typical values amount to tenths to tens of pg mL(-1) and units to one hundred pg mL(-1) for the limits of detection and determination, respectively; the measuring sensitivity increases with increasing length of the analyte chain. The analyzes of real samples from the Vltava and Elbe rivers have demonstrated that the results obtained are similar to the values published for contamination of the Elbe and other rivers in western and central Europe. The concentrations determined are of the order of units to tens of pg mL(-1) and the C(8)-C(10) acids occur most often.
Keywords: extrakce na pevné fázi; Gas Chromatography-Mass Spectrometry; Česká republika; Fluorocarbons; Solid Phase Extraction; Water Pollution, Chemical; kyseliny karboxylové; Carboxylic Acids; Rivers; chemické látky znečišťující vodu; Czech Republic; plynová chromatografie s hmotnostně spektrometrickou detekcí; Water Pollutants, Chemical; řeky; chemické znečištění vody; Environmental Monitoring; monitorování životního prostředí; fluorokarbony